(untitled) (Nusantara Medical Science Journal, 2017)
ABSTRACT Introduction: Angiogenesis plays an important role in the growth and metastasis of colorectal carcinoma, which is currently one of the targets of cancer therapy. It has been reported that the Endoglin (CD105) involved in angiogenesis and is a powerful marker for angiogenesis in colorectal carcinoma. Level Quantitative angiogenesis in peritumor and an intratumor area is important to know because it is closely related to the micro-environmental factors that influence the occurrence of cancer angiogenesis. The goal of this study to analyze the distribution pattern of angiogenesis in colorectal cancer by comparing the distribution of angiogenesis in peritumor and intratumor areas between well, moderate and poorly differentiated colorectal carcinoma, and between metastasis and non-metastatic colorectal cancer. Methods: This study analyzed fifty samples of resected adenocarcinoma colorectal. Angiogenesis was assessed by the immunohistochemical method using a primary monoclonal antibody Endoglin (CD105). Positive expression of CD105 was assessed through the CD105 protein expression in neovascular endothelial cells, while the distribution pat- tern of angiogenesis assessed by counting the positive expression of CD105 protein in hot spots by using the MVD (microvessel density) in the peritumor and intratumor areas and then performed statistical analysis. Results: There is a significant difference between the quantitative level of an- giogenesis in peritumor and intratumor areas of well (P<0.01), moderate (P<0.01) and poorly (<0.05) differentiated adenocarcinoma. The significant difference between the quantitative levels of angio- genesis in peritumor and intratumor areas of non-metastatic colorectal cancer (P<0.01) and lymph node metastases (<0.05) was found, but not in colorectal cancer with liver metastasis. Conclu- sion: Angiogenesis pattern is more concentrated in peritumor compared to intratumor areas. This showed the role of stromal cells in-angiogenesis. There is significant expression between angio- genesis in peritumor and intratumor areas. Keywords: Angiogenesis, Colorectal cancer, Endoglin (CD105)